Nueroprotection by Anesthetics in Brain Injury Models - A. D. Bocharnikov; E. A. Boeva; M. A. Milovanova; V. V. Antonova; E. I. Yakupova; A. V. Grechko (Общая реаниматология)
The aim of the study was to compare the eﬀect of sevoﬂurane and chloral hydrate on the neurological status and volume of brain damage after trauma and ischemia in experimental models of traumatic brain injury (TBI) and focal ischemic stroke (IS) induced by photothrombosis (PT).Materials and methods. The experiments were performed on mongrel Wistar rats weighing 250–300 g (N=43). There were 4 groups: the Ischemia + Sevoﬂurane group (ISSEV) (N=10), the Ischemia + Chloral hydrate group (ISCH) (N=10), TBI + Sevoﬂurane group (TBISEV) (N=13), and TBI+Chloral hydrate group (TBICH) (N=10). Ischemic brain damage was modelled using Rose Bengal (RB) dye-induced PT, and TBI was modelled using mechanical force-induced concussion.Results. MRI findings indicate lower volumes of brain damage (mm³) in rats from TBISEV group compared with the TBICH group (19±5 vs. 60±5, P<0.0001), and in the ISSEV group compared with the ISCH group (9.8±1.5 vs. 21.5±2, P=0.0016). Moreover, there was a significant difference between ISSEV and ISCH groups based on the protocol assessment of neurological status on day 14 with higher scores in ISSEV (11.4±1.8 vs. 4.9±2.6, P<0.0001).Conclusion. Taking into account the data obtained, we recommend a careful choice of anesthesia when modeling ischemic stroke and traumatic brain injury in animals. In particular, the neuroprotective eﬀect of sevoﬂurane should be taken into account in the PT and TBI models.